Optimization of Tabersonine Methoxylation to Increase Vindoline Precursor Synthesis in Yeast Cell Factories - Pamela Lemos Cruz; Natalja Kulagina; Grégory Guirimand; Johan-Owen De Craene; Sébastien Besseau; Arnaud Lanoue; Audrey Oudin; Nathalie Giglioli-Guivarc’h; Nicolas Papon; Marc Clastre; Vincent Courdavault (Molecules, 2021)
Plant specialized metabolites are widely used in the pharmaceutical industry, including the monoterpene indole alkaloids (MIAs) vinblastine and vincristine, which both display anticancer activity. Both compounds can be obtained through the chemical condensation of their precursors vindoline and catharanthine extracted from leaves of the Madagascar periwinkle. However, the extensive use of these molecules in chemotherapy increases precursor demand and results in recurrent shortages, explaining why the development of alternative production approaches, such microbial cell factories, is mandatory. In this context, the precursor-directed biosynthesis of vindoline from tabersonine in yeast-expressing heterologous biosynthetic genes is of particular interest but has not reached high production scales to date. To circumvent production bottlenecks, the metabolic flux was channeled towards the MIA of interest by modulating the copy number of the first two genes of the vindoline biosynthetic pathway, namely tabersonine 16-hydroxylase and tabersonine-16-O-methyltransferase. Increasing gene copies resulted in an optimized methoxylation of tabersonine and overcame the competition for tabersonine access with the third enzyme of the pathway, tabersonine 3-oxygenase, which exhibits a high substrate promiscuity. Through this approach, we successfully created a yeast strain that produces the fourth biosynthetic intermediate of vindoline without accumulation of other intermediates or undesired side-products. This optimization will probably pave the way towards the future development of yeast cell factories to produce vindoline at an industrial scale.